(untitled) (AL MUNAZHZHARAH, 2023)
Gugat’s divorce is the breakup of a marriage filed by a wife with the husband. The number of cases that occurred in the Kediri Regency Religious Court compared to the Talak Divorce case became the basis for the background of this research. This study aims to determine the dominant factors causing divorce lawsuits in the Kediri Regency Court area and to analyze the factors of divorce lawsuits in the Kediri Regency Religious Court. The research method used is qualitative research of an empirical nature . sources of data obtained from informants, places and events. The data collection technique in this study uses interviews and documentation, the data analysis technique used is an empirical qualitative analysis, which is something that describes the actual situation in the Kediri Regency Religious Court. Based on the results of this study, the factors causing divorce in the Kediri Regency Religious Court, the 3 most dominant factors are factors caused by the economy in 2020 reaching 2243 cases and in 2021 reaching 2146. The second is the factor of continuous disputes and quarrels in 2020 reaching 311 divorce cases and in 2021 reaching 256. And the third is to leave one of the parties in 2020 which is 241 and 2021 reached 237. the economy is less stable, plus in these 2 years there was an outbreak of covid-19 disease which made the economic downturn in the community because there were restrictions on community activities that greatly affected income or income in the community. Frequent disputes and quarrels lack of understanding or attention from the husband to the wife and make it the wife demand her rights. And improve the economy by wandering both outside Java and abroad. not a few also disagreed with one of the parties but still forced to leave to wander, from there made the estrangement of a family relationship.